A novel digital watermarking scheme using dragonfly optimizer in transform domain. (March 2021) - Shaik, Ayesha; Masilamani, V.
Abstract: In today's technologically-wise advanced environment, it is very significant for the entrepreneurs and business people to secure or protect the digital content. Their digital content can be protected legally using the copyright information such as copyrights embedded into the data. Bio-inspired computing algorithms will help find the optimal scale factor(s) by developing an appropriate fitness function and parameter selection. This article proposes a novel robust and blind watermarking method for digital images using a dragonfly optimizer. This article provides a solution for a false-positive problem using third party protection code. The proposed watermarking system outperforms the competing methods both on efficiency and efficacy measures such as experimental time, Bit Error Rate, Peak Signal to Noise Ratio, Normalized Correlation in the standard databases (Signal and Image Processing Institute (SIPI), Break Our Watermarking System (BOWS)) and also found to be robust to various image processing attacks.